Cyclodimerization versus Polymerization of Methyl Methacrylate Induced by N‐Heterocyclic Carbenes: A Combined Experimental and Theoretical Study. Issue 14 (6th March 2014) - Nzahou Ottou, Winnie; Bourichon, Damien; Vignolle, Joan; Wirotius, Anne‐Laure; Robert, Fredéric; Landais, Yannick; Sotiropoulos, Jean‐Marc; Miqueu, Karinne; Taton, Daniel
Abstract The activation behavior of two N‐heterocyclic carbenes (NHCs), namely, 1, 3‐bis(isopropyl)imidazol‐2‐ylidene(NHCiPr) and 1, 3‐bis(tert‐butyl) imidazol‐2‐ylidene (NHCtBu), as organic nucleophiles in the reaction with methyl methacrylate (MMA) is described. NHCtBu allows the polymerization of MMA in DMF at room temperature and in toluene at 50 °C, whereas NHCiPr reacts with two molecules of MMA, forming an unprecedented imidazolium–enolate cyclodimer (NHCiPr/MMA=1:2). It is proposed that the reaction mechanism occurs by initial 1, 4‐nucleophilic addition of NHCiPr to MMA, generating a zwitterionic enolate 2, followed by addition of 2 to a second MMA molecule, forming a linear imidazolium–enolate 3 (NHCiPr/MMA=1:2). Proton transfer, generating intermediate 5, followed by cyclization and release of methanol yielded the aforementioned zwitterionic cyclodimer 1:2 adduct 7, the molecular structure of which has been established by NMR spectroscopy, X‐ray diffraction, and mass spectrometry. This unexpected difference between NHCtBu and NHCiPr in the reaction with MMA (polymerization and cyclodimerization, respectively) can be rationalized by using DFT calculations. In particular, the nature of the NHC strongly influences the cyclodimerization pathway, the cyclization of 5 and the release of methanol are the discriminating step and limiting step, respectively. In the case of NHCtBu, both steps are strongly disfavoured compared with that of NHCiPr (energetic difference of around 14 and 9 kcal mol−1, respectively), preventing the cyclization mechanism from a kinetic viewpoint. Moreover, addition of a third molecule of MMA in the polymerization pathway results in a lower activation barrier than that of the limiting step in the cyclodimerization pathway (difference of around 14 kcal mol−1), in agreement with the formation of polymethyl methacrylate (PMMA) by using NHCtBu as nucleophile.